2022
DOI: 10.1111/aos.15150
|View full text |Cite
|
Sign up to set email alerts
|

Review on the possible pathophysiological mechanisms underlying visual display terminal‐associated dry eye disease

Abstract: Background: Visual display terminal (VDT) use is a key risk factor for dry eye disease (DED). Visual display terminal (VDT) use reduces the blink rate and increases the number of incomplete blinks. However, the exact mechanisms causing DED development from VDT use have yet to be clearly described. Purpose: The purpose of the study was to conduct a review on pathophysiological mechanisms promoting VDT-associated DED. Methods: A PubMed search of the literature investigating the relationship between dry eye and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 98 publications
1
13
0
Order By: Relevance
“…Previous research has identified many risk factors for DED, including aging, female sex, Asian race, environmental exposures, autoimmune diseases, allergies, hormonal imbalance, psychiatric disorders, certain classes of medications, contact lens wear, refractive surgery, and so on [2,3,10]. However, the extended use of digital display terminals (DDTs), such as computers, smartphones, or tablets, is considered to be a key risk factor for DED, mainly through impaired blinking patterns [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified many risk factors for DED, including aging, female sex, Asian race, environmental exposures, autoimmune diseases, allergies, hormonal imbalance, psychiatric disorders, certain classes of medications, contact lens wear, refractive surgery, and so on [2,3,10]. However, the extended use of digital display terminals (DDTs), such as computers, smartphones, or tablets, is considered to be a key risk factor for DED, mainly through impaired blinking patterns [11].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous studies, this study classified working hours into daily VDT working hours and weekly total working hours to investigate the risk of headache/eyestrain. 3 37 38 In a study that investigated 721 wage workers, the ORs for severe or disabling headache among individuals working ≥ 55 hours a week, compared with those working between 35 and 45 hours a week, were 1.38 and 1.63, respectively. 39 In other words, the longer the weekly total working hours, the higher the risk of headaches due to repetitive contraction of the neck and shoulders.…”
Section: Discussionmentioning
confidence: 99%
“…While the pathophysiology extends beyond the scope of the present review, it is important to briefly discuss the various contributing factors as they relate to the ability of nutrition in ameliorating symptoms associated with digital eye strain [ 6 , 44 , 49 , 57 ]. A number of excellent reviews which have discussed several putative mechanisms in more detail along with the spectrum of physiological effects can be found elsewhere [ 4 , 5 , 6 , 8 , 46 , 54 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms often range from irritation, burning, and stinging, as well as epiphora and foreign body sensations [ 63 , 64 ]. It has been well-documented that greater screen time behaviors represent a major component in developing symptoms of dry eye, often associated with lacrimal gland dysfunction and signs of evaporative dry eye disease [ 3 , 27 , 44 , 58 , 60 , 61 , 62 , 65 , 66 , 67 , 68 ]. In particular, computer usage significantly influence various dynamics of blinking patterns (such as frequency, amplitude, and complete vs. incomplete) thereby further increasing the rate of evaporation and exacerbating tear film instability [ 18 , 23 , 54 , 58 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation